2021
DOI: 10.3390/molecules26185666
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation and Diagnostic Methods for a Variety of Settings: A Comprehensive Review

Abstract: Sample preparation is an essential step for nearly every type of biochemical analysis in use today. Among the most important of these analyses is the diagnosis of diseases, since their treatment may rely greatly on time and, in the case of infectious diseases, containing their spread within a population to prevent outbreaks. To address this, many different methods have been developed for use in the wide variety of settings for which they are needed. In this work, we have reviewed the literature and report on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 162 publications
(422 reference statements)
0
4
0
Order By: Relevance
“…One included study reported on the comparison of LAMP to high-throughput next-generation sequencing for bacterial lower respiratory tract infections in humans, concluding that LAMP could be a promising option for swift and dependable clinical testing. 127 A recent review suggested that isothermal methods provide potential for high-throughput screening assays 110 ; however, assessment of throughput was lacking from all of the ONT studies included in our review, negating any formal comparison. This is another important area for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One included study reported on the comparison of LAMP to high-throughput next-generation sequencing for bacterial lower respiratory tract infections in humans, concluding that LAMP could be a promising option for swift and dependable clinical testing. 127 A recent review suggested that isothermal methods provide potential for high-throughput screening assays 110 ; however, assessment of throughput was lacking from all of the ONT studies included in our review, negating any formal comparison. This is another important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 53 , 114 Detection of AMR in bacteria can further target antimicrobial therapy by informing the choice of antimicrobials where required to manage disease, with point-of-care (POC) testing being the ultimate goal. 24 , 33 , 91 , 110 …”
mentioning
confidence: 99%
“…Sample preparation typically includes extraction, purification and concentration, which must be accomplished without sacrificing usability or reproducibility. Protocols for LFT sample preparation depend on sample type, assay, target and setting, and can be optimized for highthroughput, rapid or point-of-care testing 99 . For example, paramagnetic particle systems can be used for purification and concentration to enable automated, high-throughput testing 100 , and magnetic-beadbased commercial kits allow rapid, point-of-care sample preparation 101 .…”
Section: Review Articlementioning
confidence: 99%
“…Techniques applied for sample transformation can range from chemical modifications (sample preparation) to physical modifications (sample pretreatments) of the sample. Reviews covering many of the different methods currently available can be found the scientific literature [1][2][3]. One common technique used in conjunction with mainstream diagnostic assays is known as immunomagnetic separation (IMS).…”
Section: Introductionmentioning
confidence: 99%